EDUCATION AS A SOCIAL RIGHT: THE INCLUSION OF AUTISTIC PEOPLE IN REGULAR SCHOOLS - da Silva Candeia, Acilina (Revista Gênero e Interdisciplinaridade, 2024)
This work aims to analyze the inclusion of autistic people in regular schools. The importance of this work is to make people more interested in the school inclusion of people with autism spectrum disorder, taking into account legislation and the principle of equality, bearing in mind that the same does not only happen in isolated cases , but also in everyday life, living with people with some type of disability, whatever it may be, as we have to learn to deal with inclusion naturally. To this end, he used bibliographical and documentary research based on the analysis of doctrine, scientific articles published in periodicals and legislation applied to the topic. The approach method used was deductive since the chain of calculation used was descending, that is, the challenges and protection of people with disabilities were analyzed in a generalized way and then treated in a particular way with school inclusion. of a person with autism spectrum disorder. It is concluded that the Brazilian Federal Constitution of 1988 was responsible for institutionalizing fundamental rights and guarantees in an innovative way, being a pioneer in confirming these prerogatives to all citizens, whether they are people with disabilities or not. Thus, access to regular education, which allows contact with other children, enabling inclusion in classrooms with trained professionals, is a right for every person with a disability, such as those with ASD. In this way, inclusive education is a right guaranteed by the Federal Constitution, by infra-constitutional legislation and, above all, by the principle of equality.